The impact of online learning on mental illness among physical and health education students at Malaysian public university / Zul Amir Hanafi Ambok Welan and Ahmad Fahim Zulkifli - Ambok Welan, Zul Amir Hanafi; Zulkifli, Ahmad Fahim (Universiti Teknologi MARA, 2023)
The recent pandemic has had an impact towards students’ mental health, especially during online learning. The students have endured several types of mental illnesses such as depression, anxiety, and stress. A descriptive research design was employed to explore the variables towards participants’ mental health. A questionnaire was used to discover (1) the impact of online learning on mental illness among physical and health education (PHE) students, (2) the impact of online learning on mental illness between genders, and (3) the impact of online learning on mental illness in a different residential area of physical and health education students. About 180 students of Physical and Health Education in a local Malaysian university (n= 98, 82) comprised of males and females respectively participated in this study. The researcher used the Depression Anxiety and Stress Scale-21 (DASS-21) to identify and determine the mental health levels of the participants. Descriptive analysis (e.g., average, standard deviation, and percentages), T-Test and ANOVA were used to answer each of the research questions. This study found that only 13% of participants reported severe depression levels. Nonetheless, 32% of participants suggest that they experience a sense of extreme anxiety when learning content online. In essence, prolonged online learning contributed to the participants' tiredness, feeling intimidated, and frustration. These issues were caused by higher screen time, reduced engagement between educators and peers as well and a lack of meaningful feedback. Additionally, stress levels and depression were not influenced by the participant’s place of residence, either urban, suburban, or rural areas.